THE ROLE OF VIRTUAL AND AUGMENTED REALITY (VR/AR) TECHNOLOGIES IN TEACHING GEOMETRY (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This article examines the role of Virtual Reality (VR) and Augmented Reality (AR) technologies in teaching geometry. It highlights how immersive technologies enhance visualization, understanding, and engagement in geometry lessons, while also exploring the challenges and prospects of integrating these tools into educational practice.